(untitled) - Rosenbaum, Peter A. (New York, 2010)
As an introduction to principles of evolution, this paperback text is ideally suited as a main text for general evolution or as a supplement for general biology, genetics, zoology
Keywords: Sự phát triển (Sinh học),Evolution (Biology)